Conformationally restricted peptide mimetics by ring-closing olefin metathesis - Wakchaure, Satish; Einsiedel, Jürgen; Waibel, Reiner; Gmeiner, Peter (Synthesis-Stuttgart, 2012)
Elegant chemical methodology restricting the backbone flexibility of biologically active peptides has attracted growing interest. A practical synthetic strategy is presented to access ten-membered lactam peptide mimetics. Employing a ring-closing olefin metathesis as the key reaction step, the cyclic olefin moiety was obtained with cis configuration. Conformational investigations were performed with two model peptides. © Georg Thieme Verlag Stuttgart New York.

Synthesis, biological evaluation, and molecular docking of novel 1,3,4-substituted-thiadiazole derivatives as potential anticancer agent - Shaikh, Samin A.; Wakchaure, Satish; Labhade, Shivaji R.; Kale, Raju R.; Alavala, Rajasekhar R.; Chobe, Santosh S.; Jain, Kamlesh S.; Labhade, Hrishikesh S.; Bhanushali, Dipak D. (BMC Chemistry, 2024)
In an attempt to develop potent anti-cancer agents, a new 1,3,4-substituted-thiadiazole derivatives (8b-g), starting from 4-substituted-thiazol-2-chloroacetamides (4b-g), were synthesized and evaluated for their cytotoxic effects on multiple human cancer cell lines, including the hepatocellular carcinoma (HEPG-2), human lung carcinoma (A549), human breast carcinoma (MCF-7) and pseudo-normal human embryonic liver (L02) cancer cell lines by an MTT assay. Among all synthesized compounds, compound 8d showed the potent anti-cancer activities with GI50 values of 2.98, 2.85 and 2.53 μM against MCF-7, A549 and HepG-2 cell lines respectively as compared to standard drug Doxorubicin. Furthermore, molecular modelling studies have spotlighted the anchoring role of 1,3,4-substituted-thiadiazole moiety in bonding and hydrophobic interaction with the key amino acid residues. Therefore, these results can provide promising starting points for further development of best anti-cancer agents. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-07-12
Keywords: Anticancer agents; Antiproliferative activity; Molecular docking; Synthesis optimization; Thiazole-Thiadiazole compounds